Placental laterality and uterine artery resistance as predictor of preeclampsia: a prospective study at GMERS Medical College, Dharpur-Patan, North Gujarat, India - Jani, Parul S.; Patel, Uday M.; Gandhi, Mayur R.; Thakor, Nilesh C.; Kakani, C. R. (International Journal of Research in Medical Sciences, 2017)
Background: Placental abnormality is one of the initial events seen in patients who are destined to develop preeclampsia. The objective was to study whether ultrasonically identified; placental laterality and uterine artery resistance can be used as a predictor for development of preeclampsia. Methods:This prospective observational study was conducted at GMERS Medical College, Dharpur-Patan tertiary care teaching institute in North Gujarat from January 2013 to December 2014. A total 400 non high risk primigravida with singleton pregnancy were included, all patients with diabetes, hypertension, renal disease, and history of smoking were excluded. In all these patients, location of placenta was determined by ultrasonography at 18 to 22 weeks of gestation. Patients who had lateral placenta were subjected for colour Doppler study for determining uterine artery resistance index. All 400 patients were followed till delivery for occurrence of preeclampsia as per ACOG guidelines. All data was analyzed and statistical significance was determined by x2 test and value of p<0.05 is considered significant. Results:Out of 400 cases, 80 (20%) cases had laterally located placenta on ultra sound examination done at 18-24 weeks of gestation. Out of the 80 women with laterally located placenta, 28 (35%) developed preeclampsia. This relationship was statistically significant. All 80 patients who had lateral placenta, 26 patients had raised uterine artery resistance and out of those 26 patients, 22 developed preeclampsia and 54 had no change in uterine artery resistance. Out of those 54 only 6 had preeclampsia (p<0. 001). The sensitivity of determining uterine artery resistance as a predictive test was 84.6%, the specificity 88.8 %, positive predictive value 78.5 % and negative predictive value 92.3%. Conclusion: A chance of preeclampsia is more in patients with lateral placenta but its sensitivity and specificity increases significantly when it is combined with uterine artery velocimetric waveform study, and we can predict preeclampsia in patient who is having lateral placenta and raised uterine artery resistance.